TOWARDS A LANGUAGE OF HOPE AND POSSIBILITY: TEACHING AGAINST THE GRAIN (Author: Roger I. Simon) - Borg, Carmel; Mayo, Peter (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1993)
Roger I. Simon. TOWARDS A LANGUAGE OF HOPE AND POSSIBILITY: TEACHING AGAINST THE GRAIN. Toronto: OISE Press, 1992, 172 pp.